The Antibiotic Drug Tigecycline: A Focus on its Promising Anticancer Properties - Xu, Zhijie; Yan, Yuanliang; Li, Zhi; Qian, Long; Gong, Zhicheng (Frontiers in Pharmacology, 2016)
Tigecycline (TIG), the first member of glycylcycline bacteriostatic agents, has been approved to treat complicated infections in the clinic because of its expanded-spectrum antibiotic potential. Recently, an increasing number of studies have emphasized the anti-tumor effects of TIG. The inhibitory effects of TIG on cancer depend on several activating signaling pathways and abnormal mitochondrial function in cancer cells. The aim of this review is to summarize the cumulative anti-tumor evidence supporting TIG activity against different cancer types, including acute myeloid leukemia (AML), glioma, non-small cell lung cancer (NSCLC), among others. In addition, future clinical trials are discussed that will evaluate the security and validate the underlying the tumor-killing properties of TIG.